A new electronic diary tool for mapping and tracking spatial and temporal head pain patterns in migraine. (April 2015) - Barmettler, Gabi; Brawn, Jennifer; Maleki, Nasim; Scrivani, Steven; Burstein, Rami; Becerra, Lino; Borsook, David
Aim: We present an electronic tool for collecting data on the patterns of migraine headache onset and progression. Methods: A digitized map consisting of 44 color-coded segments was defined based on previous reports of migraine pain and the distribution of nerves in the face, head and neck. The map was overlaid on a schematic map of the face, head and neck nerves. Thirty-six patients ( N = 36, 28 female/eight male), who met ICDH-II criteria for episodic migraine and had headaches for at least three years, identified all regions where pain typically started and how pain spread and subsequently progressed. Results: Consistent with previous findings, throbbing was the most prevalent quality of migraine pain, always present in 70% of patients surveyed. For the 70% of the patients with throbbing pain, the temple was the onset site of throbbing pain, with no significant difference in the laterality of onset site (58.3% on the right vs. 55.6% on the left hemisphere). The tool was able to capture patterns of pain distribution for throbbing and pressure headache pain and also may be used to assess the change in the pattern of the pain distribution as the disease progresses. Discussion: The pain map survey may be a useful tool for recording and tracking the temporal pattern of migraine onset both for clinical and research purposes. The tool could be used to create maps of pain locations on a large population scale and thus will be a very useful tool in correlating the temporal nature of headache symptoms with potential mechanisms of disease evolution.